Mapeamento de QTL para resistência a parasitas e características de crescimento nos cromossomos cinco e sete de uma população experimental F2 de bovinos Gir x Holandês - Gasparin, Gustavo (Universidade Federal de São Carlos, 2007)
The large amount of phenotypic variability between Bos primigenius taurus and Bos primigenius indicus cattle, which had diverged hundreds of thousands of years ago and since then have been explored by men through artificial selection of the breeds to milk and meat production, allows the development of crossbreeds, since there is no reproductive isolation between these subspecies. It is known that part of the described differences for productive and parasite resistance traits among the breeds is under genetic control, and that is possible to distinguish genetically superior individuals from the others of the population with the combined use of molecular genetics and traditional livestock production programs. Since in Brazil the economy is largely influenced by agribusiness, once bovine meat exportation alone generated US$2.5 bilion in 2004, the search and identification of chromosomic regions that control al least part of the variation of these quantitative economic traits (QTL, Quantitative Trait Loci), like birth weight and weight gain, and also regions that influence resistance to parasites, is of great concern. The objective of the present study was to map QTLs for growth traits and resistance to gastrointestinal endoparasites and external parasites, like the tick (Riphicephalus (Boophilus) microplus) and the beef worm (Dermatobia hominis) using microsatellite markers to scan bovine chromosomes five and seven in a F2 Gir x Holstein experimental population. On chromosome five, a significant (P < 0.01) QTL for birth weight and one suggestive (P < 0.05) for resistance to tick count during the rainy season were detected. On chromosome seven, it was identified an indicative QTL (P < 0.10) for tick count in the dry season. In both cases, a significant dominance deviation was observed, suggesting that part of the genetic variation must be atributed to allele combinations. The favorable allele for resistance in chromosome five was from the Gir parental and on chromosome seven, from Holstein, which is a surprising result, since the zebu breeds were traditionally considered as the solely source of tick resistance. No QTL was associated to resistance to endoparasites or to the beef worm. The application of these informations still demands the reduction of confidence intervals for the QTLs locations and validation in other populations.
Keywords: Genética animal; Animais - melhoramento genético; QTL; Bovinos - parasitas; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL